Knowledge, attitude and preventive practices of hepatitis B infection among health trainees, northern region of Ghana - Francis Kronzu Cudjoe; Tanko Abdulai; Abdul-Samed Mohammed; Sophia Twiaku; Michael Yaw Amoakoh (International Journal Of Community Medicine And Public Health, 2026)
Background: Hepatitis B virus (HBV) infection remains a major global health challenge, causing chronic liver diseases such as cirrhosis and hepatocellular carcinoma. Despite the availability of a safe and effective vaccine, infection rates remain high, particularly among healthcare workers and trainees. This study assessed the knowledge, attitude, and preventive practices regarding hepatitis B infection among health trainees at the University for Development Studies (UDS), Tamale, Ghana. Methods: A cross-sectional study was conducted among 400 health trainees selected through stratified random sampling from six schools and faculties within the UDS Dungu Campus. Data were collected using a structured questionnaire and analysed with SPSS version 23. Descriptive statistics summarized participants’ characteristics, while Chi-square and multivariable logistic regression identified factors associated with preventive practices. Statistical significance was set at p